2020
DOI: 10.1039/c9cy02407g
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube-supported Cu-based catalysts for oxidative carbonylation of methanol to methyl carbonate: effect of nanotube pore size

Abstract: The inner diameter of CNTs significantly affected the location, dispersion, autoreduction and stability of Cu species and thus the catalytic activity and stability for oxidative carbonylation of methanol to dimethyl carbonate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 49 publications
2
12
0
Order By: Relevance
“…Zhao et al used copper oxide nanoparticles supported on carbon nanotubes to accomplish such a transformation. 16 The authors used nanotubes with three different diameters (2–5, 5–10, and 20–50 nm) and found that, although all of them gave high selectivity to dimethyl carbonate, catalytic activity increased with decreasing pore diameter. This activity was attributed not only to the better dispersion of nanoparticles in the smaller pores but to the higher stability of reduced copper species, which was confirmed by XRD and XPS.…”
Section: Confinement In Pores and Cavitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhao et al used copper oxide nanoparticles supported on carbon nanotubes to accomplish such a transformation. 16 The authors used nanotubes with three different diameters (2–5, 5–10, and 20–50 nm) and found that, although all of them gave high selectivity to dimethyl carbonate, catalytic activity increased with decreasing pore diameter. This activity was attributed not only to the better dispersion of nanoparticles in the smaller pores but to the higher stability of reduced copper species, which was confirmed by XRD and XPS.…”
Section: Confinement In Pores and Cavitiesmentioning
confidence: 99%
“…The concept of confinement has now expanded beyond zeolites, and it has also been observed inside the porous channels of mesoporous silica 11–13 and carbon nanotubes, 14–16 for instance. Such materials feature pores that are connected to the bulk reaction medium, generating gradients of diffusion rates that play important roles in the reactivity of substrates.…”
Section: Introductionmentioning
confidence: 99%
“…9 In recent studies by our group, chlorine-free copper sources, like cupric acetate and cupric nitrate, have been impregnated into numerous forms of carbon materials and further pyrolyzed and reduced to prepare Cu/C catalysts, which showed potential activity for the oxidative carbonylation of methanol along with the negligible corrosion of equipment. 4,10–13 In these catalysts, reduced Cu 2 O and metallic Cu species were reported to serve as active species. Also, the amount of Cu 2 O or Cu and the chemical environment are strongly influenced by the surface properties of the carbon support, such as the presence of surface oxygen-containing groups, 14 carbon defects, 15 heteroatom doping, 16 and so on.…”
Section: Introductionmentioning
confidence: 99%
“…This means that the particles tend to agglomerate during catalytic processes. 4 However, various mesoporous materials, such as ordered mesoporous carbon (OMC), 17 mesoporous spherical carbon (MSC), 11 carbon nanotubes (CNTs) with mesoporous interiors, 12,13 and so on, were reported to successfully confine relatively small and uniform Cu nanoparticles in their mesopore channels. For example, 2.9 nm Cu nanoparticles with 9% Cu loading were observed to be confined in the 3.6 nm interconnected mesopores of OMC, acting as an effective catalyst for the oxidative carbonylation of methanol.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Recently, development of effective catalysts to produce DMC through oxidative carbonylation of methanol, which is thermodynamically favorable has received greater attention. [6][7][8][9][10][11][12][13][14][15][16][17][18] Being, chloride-free, CuY zeolite has shown greate potential to obtain high activity and excellent selectivity for oxidative carbonylation reaction. [16][17][18][19][20][21][22][23] Generally, Cu exchanged zeolite Y, CuY was prepared by ion-exchange of NaY zeolite with the ammonia solution of copper nitrate, followed by calcination at high temperatures in an inert atmosphere.…”
Section: Introductionmentioning
confidence: 99%